Preference of the patient’s family for family-centred care in a paediatric hospital - Tauseef, Usman; Anjum, Misbah; Khoso, Zubair Ahmed; Ahmed, Syed Habib; Noor, Noshaba; Jalil, Muniba (Journal of the Pakistan Medical Association, 2023)
Objective: To explore the dimensions of family-centred care preferred by families of paediatric inpatients in a public healthcare setting. Method: The qualitative study was conducted at the National Institute of Child Health, Karachi, from October 2021 to August 2022, and comprised family members of the hospitalised children. Data was collected through three focus group discussions that were guided by a semi-structured questionnaire. Using the five-step Fereday and Muir-Cochrane guidelines, data was coded and subjected to thematic analysis. Results: Of the 21 subjects, 13(62%) were males and 8(38%) were females. The overall mean age was 32.24±7.58 years (range: 18-50 years). In terms of relationship with the patient, 9(43%) were fathers and 6(28.6%) were mothers. Each focus group discussion had 7(33.3%) subjects. Thematic analysis showed that the participants perceived family-centred care positively. Eight categories emerged depicting family perception and experience of family-centred care in a tertiary-care setting. Conclusion: The participants perceived family-centred care respectful and empathic towards patients' families, making them integral care team members. Key Words: Delivery of health care, Paediatrics, Personal satisfaction, Parents, Family, Patient-centred care.